PELAKSANAAN PENGAWASAN DAN PENGAMATAN PUTUSAN PEMIDANAAN BERSYARAT OLEH HAKIM PENGADILAN NEGERI PEKANBARU - Muliani, Kristin; Lestari, Maria Maya; R, Mukhlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Courts as one law enforcement agency is executing judicial authority in charge of organizing the judiciary to uphold law and justice based Pancasila. At every court judges are given specific tasks to assist the chairman in the supervision and observation of court decisions that impose criminal punisment of deprivation of liberty, especially decision conditional. With the conditional criminal decisions handed down in the District Court of Pekanbaru there should be an implementation decision to ensure that court decisions have been implemented properly. Implementation of monitoring and observation conditional sentencing decision by District Court Judge Pekanbaru felt not and as it should be. This is because there are still many obstancles fased by the Supervisory Judge and the Court Observer.This research is a Yuridical Sosiologis research, which is a type of research aproach by looking in term of legislation and the fact that occur in the field in accordance with the problem studied. Sources of data used in sociological research is the primary data source of data that can be divided into primary, secondary and tertiary data. Techniques used in data collection are interviews and literature study. While the analysis techniques used is a qualitative manner, the method of duductive thinking.Of the research problem, there are three main things that can be inferred. First, the implementation of the monitoring and observation of the vendict setencing by District Court Judge Pekanbaru should need to be increased again. For supervision and observation by the judge is veri importaint element and the last in the law enforcement process. Secoudly, in terms of overcoming obstancles encountered in the implementation of the Court of Pekanbaru is the legal factors,namely the absence or lack of the convict parole, and law enforcement factors is the minimum number of Judge and bustle supervisors and observers and the lack of coordination and cooperation among the various law enforcement agencies. Third, the effortsmade to evercome the obstacles faced, no attempt is made to overcome the obstacles encountered both in terms of legal factors law enforcement agencies. My suggestion should be made immediately clear legislation and organize the details of the standard operating procedures.